The Influence of the Personality Traits and Sociodemographic Ceo Characteristics on Performance of Smes: Evidence from Chile - Espinosa-Mendez, C (Emerald Publishing, 2022)
Purpose: In this paper the authors study how sociodemographic characteristics and personality traits of the Chief Executive Officer (CEO) impact financial performance in small and medium enterprises (SMEs) in an emerging economy such as Chile. Design/methodology/approach: The authors applied a questionnaire to 185 Chilean SME CEOs during 2017 concerning sociodemographic characteristics (gender, age, experience and marital status), personality traits (extraversion, responsibility, openness to experience, agreeableness, and neuroticism) and firm characteristics. Findings: The authors find that some sociodemographic characteristics (gender and age) significantly impact SME performance. The authors find no significant connection between personality traits and firm performance. Originality/value: This paper contributes to the business literature by investigating how sociodemographic variables and personality traits of the CEO are related to SME financial performance; by providing new evidence on the relationship between CEO characteristics and firm performance, mostly centered on developed economies, in the context of an emerging economy; and allowing for a better understanding of how CEO decisions impact firm performance. © 2022, Emerald Publishing Limited.